Barriers and Facilitators for Setting Upper Limb Reconstruction Services. - Troisi, Luigi; Berner, Juan Enrique; Vizcay, Macarena; Pajardi, Georgio Eugenio (International Journal of Clinical Research, 2022)
Microsurgical limb reconstruction is a complex surgical technique that aims to preserve an extremity that has been affected by acquired conditions, such as trauma or cancer. It involves the transfer of free tissue flaps, which are micro-surgically revascularized in the recipient site to reconstruct a variety of defects. This can be not only technically demanding for the surgeon leading this type of procedure but also requires a well-set-up perioperative team and service. This article aims to present the experience of the first author setting up a new microsurgical service.